OTS 2023 Sodobne informacijske tehnologije in storitve: Zbornik 26. konference (University of Maribor Press, 2023)
OTS 2023 Advanced information technologies and services: Conference proceeding of the 26th conference. In the proceedings of the twenty-sixth OTS 2023 conference, we find the IT experts contributions, in which new insights and trends in the development, implementation, adaptation and management of information systems are presented, as well as practical successful approaches and praven best practices. Contributions address the areas of architectural challenges, classical, generative, and deep artificial intelligence, modem web- or mobileuser interfaces, as well as traditional, serverless and decentralized backend systems. The topics also include providing an appropriate scalable environment for them and automated testing, quality assurance and delivery by proactively addressing the most common cyber-attacks. One of the main topics remains data technologies in the form of classic databases, data lakes and efficient collection, processing, and big data visualisation. Contributions thus continue to enable a better connection between IT experts, informatics, architects and developers of advanced IT solutions and services, as well as the academia and industry.